Le Fort I and nasal fracture, primary reduction, and secondary revision saddle nose: A case report - Al Hafiz; Wahyu Julianda (Faculty of Medicine, Universitas Islam Indonesia, 2023)
Maxillofacial trauma is a common clinical situation in emergency rooms. Lesions involving the maxillofacial complex pose a significant public health challenge, not only due to their costs but also because of the potential functional and aesthetic issues that patients may experience. While some fractures are more suitable for delayed treatment, others necessitate immediate attention, requiring intervention within 24 hours of the trauma occurrence. Different types of reduction and fixation exist depending on the patient’s age, location, type of fracture, and the surgeon’s preferences. We reported a case of a 20-year-old female patient diagnosed with Le Fort I bilateral fracture and closed nasal fracture followed by saddle nose. The patient was managed with open reduction internal fixation and closed reduction nasal bone. The saddle nose in the patient was managed four months later by augmentation rhinoplasty with rib cartilage and pearl fat graft. Proper management of Le Fort I fracture and nasal fracture accompanied with saddle nose by open reduction internal fixation and augmentation rhinoplasty with rib cartilage and pearl fat graft can restore occlusion and improve symmetrical, proportional facial aesthetics, which is the indicators of a successful holistic maxillofacial trauma management.